Hepatic veno-occlusive disease may develop in secondary iron overloaded mice after allogeneic hematopoietic stem cell transplantation with total body irradiation - Yeom, Mi Young (Blood Res, 2015)
BACKGROUND: The outcome of hematopoietic stem cell transplantation (HSCT) is poor in patients with secondary iron overload (SIO). We evaluated the relationship between SIO and veno-occlusive disease (VOD) in an animal model with radiation for HSCT. METHODS: We used a 6-week-old female BDF1 (H-2(b/d)) and a male C57/BL6 (H-2(b)) as recipient and donor, respectively. Recipient mice were injected intraperitoneally with 10 mg of iron dextran (cumulative doses of 50 mg, 100 mg, and 200 mg). All mice received total body irradiation for HSCT. We obtained peripheral blood for alanine transaminase (ALT) and liver for pathologic findings, lipid hyperoxide (LH) as reactive oxygen species (ROS), and liver iron content (LIC) on post-HSCT day 1 and day 7. The VOD score was assessed by pathologic findings. RESULTS: ALT levels increased depending on cumulative iron dose, with significant differences between days 1 and 7 for mice loaded with 200 mg of iron (P<0.01). LH levels significantly increased in mice loaded with 200 mg of iron compared to those in other groups (P<0.01). For mice loaded with 100 mg of iron, the LH level depended on the radiation dose (P<0.01). There was a statistically significant relationship among ALT, LH, and LIC parameters (P<0.05). Pathologic scores for VOD correlated with LIC (P<0.01). CONCLUSION: Livers with SIO showed high ROS levels depending on cumulative iron dose, and correlations with elevated liver enzyme and LIC. The pathologic score for VOD was associated with the LIC. Our results suggest that SIO may induce VOD after HSCT with irradiation.